PENGEMBANGAN GAME EDUKASI 2 DIMENSI BERBASIS RPG PADA MATERI TOPOLOGI JARINGAN UNTUK SISWA KELAS XI TKJ SMKN 2 BANGKALAN - Jumadi, Ahmad; Tahir, Muhlis (Politeknik Negeri Batam, 2024)
Based on the results of observations and interviews with network device subject teachers at SMKN 2 Bangkalan, it was found that learning network topology in class XI Computer Network Engineering only used teaching modules, making students feel bored and limited to learning at school. To overcome this, the research developed a role-playing game (RPG) for network topology learning using the Game Development Life Cycle (GDLC) model, which includes six phases: initiation, pre-production, production, testing, release, and maintenance. This game was tested by material and media experts using ISO 25010, and also tested on small and large groups, with results showing high feasibility. Based on the research results, this RPG game is considered suitable for use as a learning medium and can be disseminated to help students understand network topology in a more interesting and interactive way.